Characterization And Properties Of Synthesized And Sintered Carbonated Hydroxyapatite - Ismail, Yanny Marliana Baba (2011)

(untitled)
B-type Carbonated Hydroxyapatite (CHA) was successfully synthesized via nanoemulsion method, through dropwise (DW) and direct pouring (DP) techniques. The carbonate content in DP (8.60%) was higher than DW (7.85%). Both techniques produced nano-sized powders with variation in shapes of particles. It was also found that at temperature (≤ 40°C), the CHA powders were angular while above this critical temperature mixture of rods and angular shape was produced. Room temperature synthesis was better as they produced nano-size CHA with larger surface area. Sintering was then performed on pure CHA, CHA+Mg(OH)2, HA and HA+Mg(OH)2, samples which was cooled down with and without wet CO2 atmosphere to produce different type of carbonate substitution in the structure.